2021
DOI: 10.3390/ijms22168366
|View full text |Cite
|
Sign up to set email alerts
|

G2-S16 Polyanionic Carbosilane Dendrimer Can Reduce HIV-1 Reservoir Formation by Inhibiting Macrophage Cell to Cell Transmission

Abstract: Human immunodeficiency virus (HIV-1) is still a major problem, not only in developing countries but is also re-emerging in several developed countries, thus the development of new compounds able to inhibit the virus, either for prophylaxis or treatment, is still needed. Nanotechnology has provided the science community with several new tools for biomedical applications. G2-S16 is a polyanionic carbosilane dendrimer capable of inhibiting HIV-1 in vitro and in vivo by interacting directly with viral particles. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The 2 nd generation carbosilane dendrimer, composed of a silica core surrounded by 16 sulphonate moieties (G2-S16), directly suppressed the viruses within macrophages and also inhibited viral spreading from the macrophage to other immune cells. 250 Thus, the therapeutic dendrimer NPs exert the ability to inhibit infected macrophage reservoirs and could be used in antiretroviral therapy. Excessive inflammation and multiorgan failure due to proinflammatory cytokine-mediated cytokine storms can result in fatal consequences in patients suffering from the recent pandemic SARS-CoV-2 virus.…”
Section: Key Immune Components and Their Modulation With Therapeutic ...mentioning
confidence: 99%
“…The 2 nd generation carbosilane dendrimer, composed of a silica core surrounded by 16 sulphonate moieties (G2-S16), directly suppressed the viruses within macrophages and also inhibited viral spreading from the macrophage to other immune cells. 250 Thus, the therapeutic dendrimer NPs exert the ability to inhibit infected macrophage reservoirs and could be used in antiretroviral therapy. Excessive inflammation and multiorgan failure due to proinflammatory cytokine-mediated cytokine storms can result in fatal consequences in patients suffering from the recent pandemic SARS-CoV-2 virus.…”
Section: Key Immune Components and Their Modulation With Therapeutic ...mentioning
confidence: 99%
“…On the other hand, the use of the labeled sulfonate dendrimer G2‐S16‐FITC (Figure S11; Gutiérrez‐Ulloa et al, 2020) enabled the analysis of the internalization of this type of anionic dendrimer in macrophages and justify the inhibition of infection observed from infected macrophages to healthy lymphocytes. Thus, G2‐S16 prevents the formation of HIV reservoirs (Relano‐Rodríguez et al, 2021). The application of G2‐S16‐FITC to the epithelial vaginal tissue of BALB/c mice confirmed that this family of dendrimers crosses this barrier reaching the circulatory system.…”
Section: Pharmaceutical Applications Of Carbosilane Dendritic Moleculesmentioning
confidence: 99%